2022
DOI: 10.1021/acsabm.2c00303
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Fibronectin-III10–DNA Origami Nanofibers Promote Cell Adhesion and Spreading

Abstract: The integration of proteins with DNA nanotechnology would enable materials with diverse applications in biology, medicine, and engineering. Here, we describe a method for the incorporation of bioactive fibronectin domain proteins with DNA nanostructures using two orthogonal coiled-coil peptides. One peptide from each coiledcoil pair is attached to a DNA origami cuboid in a multivalent fashion by attaching the peptides to DNA handles. These structures can then be assembled into one-dimensional arrays through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The fibronectin secretion of HDFs seeded on the surface of samples was then measured. Fibronectin is a ubiquitous protein in the extracellular matrix, which could increase the expression of integrins during wound healing to accelerate the STI process . Immunofluorescence staining was performed on HDFs seeded on three steps of surfaces after culture for 7 days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibronectin secretion of HDFs seeded on the surface of samples was then measured. Fibronectin is a ubiquitous protein in the extracellular matrix, which could increase the expression of integrins during wound healing to accelerate the STI process . Immunofluorescence staining was performed on HDFs seeded on three steps of surfaces after culture for 7 days.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, fibronectin protein expression was demonstrably increased in HDFs grown on the CCN2@MSNs-Ti surface compared with S-Ti and MAO-Ti (Figure S4A,C). The cytoskeleton formation and fibronectin secretion ability of fibroblasts could facilitate STI development because they could affect the adhesion and proliferation of cells. , Based on the positive results above, the cell adhesion and proliferation on the surface of CCN2@MSNs-Ti were then measured. The CFSE labeling method was used to evaluate the initial cell adhesion by measuring the fluorescence intensity with a fluorescent plate reader.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have demonstrated higher order assembly of static DNA origami structures(19,20,45), and recent studies have extended to dynamic assemblies(2227) . Inspired by the development of peptide-DNA conjugates for DNA origami assembly (39), here we used coiled-coil peptides as a useful adhesive for higher order self-assembly of dynamic devices where orientational control, and hence assembly structure control, can be engineered by organizing peptides into patches or patterns. Recent interest and advances in the colloidal or patchy particle assembly of DNA origami structures(46,47) can provide further guidance towards more complex and functional assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…The responsive nature of our assemblies and the combination of peptide and nucleic acid interactions to achieve assembly and actuation suggest these dynamic assemblies could serve as a useful platform to design adaptive materials that change shape or properties in response to amino acid or nucleic acid-based triggers or other environment stimuli. In particular, the use of coiled-coils could be an attractive approach for interfacing with a variety of proteins (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation